PEMBAGIAN MASKER BAGI PENGENDARA SEBAGAI UPAYA PENCEGAHAN PENULARAN COVID-19 DI DESA KEBAMAN KECAMATAN SRONO BANYUWANGI - Eka Suci Daniyanti; Enggal Sari Maduratna; Nailufar Firdaus (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2021)
The number of patients infected with the Covid-19 virus continues to increase day by day, various efforts have been made with the aim of controlling the transmission of the virus. Adapting to new habits by always wearing masks is one of the efforts driven by the government to break the chain of transmission of COVID-19. Get used by wearing a mask, especially when doing outside activities, you will avoid the risk of contracting the covid-19 virus, splash droplets / body fluids that come out of the body of someone infected covid-19 virus either from the nose or mouth through sneezing, coughing will be able to transmit the virus because When coughing or sneezing, droplets can be inhaled and stick to the surface of objects or hands. The use of masks is very important as a prevention of Covid-19 transmission, when in crowds or stay close together in a public places, because masks can dispel droplets that come out when talking, exhaling, coughing or sneezing so that the transmission of the virus will be reduced. Community service activities carried out were distributing masks and stickers about the importance of using masks. A total of 200 masks were distributed to the public, especially motorists who are doing activities outside the home.